Bio-Pots: Innovation in biodegradable pots, based on a business model in a circular economy - Suárez Colores, Z. P.; Barrios Reyes, I.; Alaniz Lara, G. Y.; Dolores Ruiz, E.; Salazar Gómez, J. F. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2026)
The growing environmental problems arising from the use of plastics in horticulture and the proliferation of water hyacinth in bodies of water demand sustainable and innovative alternatives. The aim of this study is to design and assess the feasibility of biodegradable pots made from plant waste such as banana rhizome (Musa paradisiaca), cuajilote bark (Parmentiera aculeata) and water hyacinth (Eichhornia crassipes), under the project called Bio-Pots. The research was conducted using an experimental-descriptive approach, which included the collection, processing and mixing of raw materials, as well as tests of mechanical resistance, permeability and degradation time under controlled soil conditions. Preliminary results showed that pots made with a balanced proportion of 40% banana rhizome, 35% water hyacinth, and 25% cuajilote bark achieved a degradation time of 6 to 8 months, which represents an efficient alternative to the 500-year persistence of polypropylene pots. Likewise, resistance tests indicated that the product can support up to 1 kg of weight, sufficient for ornamental crops and agricultural transplants. In terms of permeability, improved substrate drainage was observed without compromising moisture retention. These characteristics make Bio-Pots a product with high potential for application in the nursery, agricultural, and ornamental industries, offering a solution that combines sustainability, social and solidarity-based circular economy, and the use of invasive species. It is concluded that this innovation not only reduces plastic pollution and the impact of invasive plants, but may also generate economic opportunities for rural communities through the management of plant waste.
Keywords: Biodegradable, Sustainability, Circular economy, Social and solidarity economy, Innovation.